Analysis of Essential Elements in Commercially Important Lobster Species Collected From Coastal Areas of Karachi City, Pakistan - Tuba Kamal; Muhammad Asad Khan Tanoli; Majid Mumtaz; Sara Ayub (Journal of Pharmacy and Nutrition Sciences, 2015)
The study was undertaken to assess the sea food product having attractive environmental effects as they are important source of nutrients in human diets. A part from delicacy crustacean is of high value and appreciated food items, representing an important economic source in the last decade. The chemical composition and nutritional value of crustacean heavily investigated worldwide and composition benefit to human health have been much promoted. The lack of macronutrients in human leads to improper enzyme mediated metabolic functions and results in organo-malfunctions, chronic diseases and ultimately death. The aim of this study is to quantify the essential elements like Copper, Zinc, Sodium, Potassium, Calcium and Magnesium in different body parts of male and female lobster species. For this purpose lobster species were collected in year 2011 to 2013 from the different fish harbor of Karachi city. Atomic Absorption Spectroscopy (AAS) technique was used to analyze the Cu, Zn, Ca and Mg while Flame photometer was used to quantify the Na and K. The results were compared on the basis of WHO/ FAO values. The concentrations of selected essential metals were within the normal range in all the analyzed samples. Pearson correlation were applied to find out the inter metal relationship in different parts of lobster at significant level p < 0.01 or p < 0.05 and were found maximum relationship between the metals Cu:Zn, Zn:Na, Zn:K, Na:K, Na:Ca, Na:Mg, K:Mg and Ca:Mg in whole three years studied indicate that the strong correlation between the macronutrients and increasingly adverse impact of industrialization and urbanization on the commercially important lobsters community day by day.